Incorporating Volunteering Into Treatment for Depression Among Adolescents: Developmental and Clinical Considerations - Ballard, Parissa J.; Daniel, Stephanie S.; Anderson, Grace; Nicolotti, Linda; Caballero Quinones, Elimarie; Lee, Min; Koehler, Aubry N. (Frontiers in Psychology, 2021)
Volunteering, or taking part in unpaid work for the benefit of others, can be a powerful positive experience with returns to both individual well-being and community projects. Volunteering is positively associated with mental health in observational studies with community samples but has not been systematically examined as a potential part of treatment interventions with clinical adolescent samples. In this manuscript, we review the empirical evidence base connecting volunteerism to mental health and well-being, outline potential mechanisms based in the theoretical literature from developmental science, and discuss the existing clinical approaches that support community volunteering as a part of treatment. Drawing on this review, we propose that including volunteering as a component of clinical treatment approaches for adolescent depression can be a powerful intervention for adolescents.